2023
DOI: 10.1039/d3cc04051h
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecular assembly strategy towards organic luminescent materials

Chenjia Yin,
Zi-Ang Yan,
Xiang Ma

Abstract: Supramolecular luminescent materials with different dimensionality usually exhibits different optical properties as well as their potential applications in various fields. Recent reports showed that non-covalent interactions are useful tools to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…In addition to the confinement of a guest, its orientation inside the host can also be employed to tune the optical properties. For instance, Arduini et al reported a reversibly fluorescence-tunable calix [6]arene 24based pseudorotaxanes by commutating the orientation of the axle 25. With increasing time delays, the absorption band intensity of 433 nm progressively decreases accompanied by a new band appearing at 490 nm, corresponding to two orientational isomers, 24-25-D and 24-25-U, respectively.…”
Section: Guests-modulated Color-tunable Ma-based Slmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the confinement of a guest, its orientation inside the host can also be employed to tune the optical properties. For instance, Arduini et al reported a reversibly fluorescence-tunable calix [6]arene 24based pseudorotaxanes by commutating the orientation of the axle 25. With increasing time delays, the absorption band intensity of 433 nm progressively decreases accompanied by a new band appearing at 490 nm, corresponding to two orientational isomers, 24-25-D and 24-25-U, respectively.…”
Section: Guests-modulated Color-tunable Ma-based Slmsmentioning
confidence: 99%
“…During the past few decades, supramolecular luminescent materials (SLMs), assembled from single or multi-component systems by noncovalent interactions (including π-π stacking, CÀ H•••π, metal-π, hydrogen bonding, charge transfer (CT) interactions, etc), have been extensively investigated. [6] For instance, in 2019, Tian and Ma proposed the concept of "Assembling-Induced Emission", which refers to controlling the molecular configuration or accumulation via supramolecular dynamic assembly, thus controlling the emission of assemblies. [7] In comparison with traditional organic luminescent materials, luminescent materials in supramolecular systems have the following advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Noncovalent interactions (NCIs) of different kinds are many times at the very heart of conformational preferences , and behind the existence of ubiquitous intermolecular assemblies for different functionalities or purposes. The importance of hydrogen bonds (HBs) in the Watson–Crick–Franklin motifs, the HBs and stacking interactions in biomaterials design, , or the NCIs in artificial structures such as MOFs and COFs or graphene engineering is well known, to cite only some representative examples beyond the awesome properties of water. In this sense, despite the recognized difficulty in accurately describing them because of the energy range of these interactions and their complex physical background, noncovalent interactions (with different names) have been a key topic in chemistry from the 19th century up to the very diverse and rich present, and the HB in particular has been a part of the common chemical vocabulary since its inclusion in one of the most famous chemistry textbooks of all time. , …”
mentioning
confidence: 99%
“…2 (2) Stable covalent bonds are formed between the RTP species and the matrix to reduce the nonradiative process. 3 (3) Fixation of the RTP centers in nanospace to facilitate efficient spatial restriction. 4…”
mentioning
confidence: 99%